Appreciation of Diversity and Pancasila Values and Their Implications for the Moral Development of Students at SMA Negeri 10 Palembang - Vidia Nur Vadilla (LPPM Institut Studi Islam Sunan Doe, 2022)
As a country that has diversity, we must be able to live up to the values ​​contained in Pancasila, as a way to provide a moral foundation for the nation's children. The purpose of this study was to find out how the appreciation of diversity and Pancasila values ​​and their implications for the moral development of students at SMA Negeri 10 Palembang. Data collection techniques through observation and documentation. This research was conducted at SMA Negeri 10 Palembang. Based on the results of observations that have been made, SMA Negeri 10 Palembang has diversity starting from ethnicity, culture, religion and social status. With the diversity that exists in SMA Negeri 10 Palembang, the appreciation of Pancasila values ​​has been done very well to maintain unity in the midst of existing diversity. The implication for moral development is that SMA Negeri 10 Palembang has good moral development.